Indicators of Spiritual Mortality in Religious Practice: A Conceptual Study of Theological and Psychological Perspectives - Sohibul Barkah; Cicih Sarinengsih; Patrizio Sanna; Diah Siti Rodyah; Moch. Mahdiyan Nasikhin; Atin Priatin Munawaroh; Apriyanin; Resa Ineukeu Kusumahwati (International Journal of Sociology of Religion, 2025)
This paper attempts to re-read, rather carefully, what spiritual death actually means in religious practice. The focus is not just on whether or not religious activity is crowded, but on something that often goes unnoticed: the depth of the inner experience. In many places, for example, religious studies are becoming more accessible, mosques are full at certain times, and even da'wah content is circulating on social media. But at the same time, there is an impression that the intensity is not always directly proportional to the quality of the experience. That is where this research departed. The approach used is qualitative through library research. The Book of Al-Hikam is used as the main foothold to explore the idea of the death of the heart, then read side by side with the thoughts of other scholars as well as contemporary psychological frameworks such as religious/spiritual struggles, meaning-making, and spiritual numbness. This process is not always linear, but sometimes it shows an interesting tension between the symbolic language of Sufism and the analytical concept of psychology. The findings lead to one rather disturbing but important conclusion: religious practices that are not deeply internalized risk giving rise to spiritual stagnation, even contradictions in everyday moral attitudes. This is where this research tries to contribute, although certainly not perfectly, by bringing together classical Sufism and modern psychology in one more complete conversation about the inner dynamics of religion.